RECENT MANUFACTURING TECHNIQUES OF METALLIC BIOMATERIALS - Singh, Bhavana; Trivedi, Vaibhav; Goel, Ankur (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Additive Manufacturing (AM) which is universally known by the acronym of 3D printing has transformed the process of producing metallic biomaterials, enabling the production of complex, customized, and high-performance implants. The range of applications of AM is increasing across all sectors due to its ability of producing defects free products and tailoring the properties as per the requirement. In order to gather most of the metallic applications of AM and its technicality at one place, this review is dedicated to AM techniques that are applied for the creation of metallic biomaterials, particularly for biomedical implants. These laser-based AM techniques allow precise control over microstructure, porosity, and mechanical properties, facilitating the development of patient-specific implants with enhanced biocompatibility and durability. The review delves into the suitability of various materials, let say alloy that contains titanium, cobalt, and chromium, for AM processes, highlighting their advantages in respect to mechanical strength, high corrosion resistance, and compatibility with biological tissues. Additionally, it addresses the challenges associated with AM, including thermal stress management, surface finish optimization, and quality control. The findings underscore the significant potential of AM in advancing medical technology, tailored to individual patient needs that will certainly help in developing understating for the creation of future biomaterial with ease.